A Chimera Containing CD4+ and CD8+ T-Cell Epitopes of the Leishmania donovani Nucleoside Hydrolase (NH36) Optimizes Cross-Protection against Leishmania amazonesis Infection - Alves-Silva, Marcus Vinícius; Nico, Dirlei; Morrot, Alexandre; Palatnik, Marcos; Palatnik-de-Sousa, Clarisa B. (Frontiers in Immunology, 2017)
The Leishmania donovani-nucleoside hydrolase (NH36) and NH A34480 of L. amazonensis share 93% of sequence identity. In mice, the NH36 induced protection against visceral leishmaniasis is mediated by a CD4+ T cell response against its C-terminal domain (F3). Besides this CD4+ Th1 response, prevention and cure of L. amazonensis infection require also additional CD8+ and regulatory T-cell responses to the NH36 N-terminal (F1 domain). We investigated if mice vaccination with F1 and F3 domains cloned in tandem, in a recombinant chimera, with saponin, optimizes the vaccine efficacy against L. amazonensis infection above the levels promoted by the two admixed domains or by each domain independently. The chimera induced the highest IgA, IgG and IgG2a anti-NH36 antibody, IDR, IFN-γ and IL-10 responses, while TNF-α was more secreted by mice vaccinated with F3 or all F3-contaning vaccines. Additionally, the chimera and the F1 vaccine also induced the highest proportions of CD4+ and CD8+ T cells secreting IL-2, TNF-α or IFN-γ alone, TNF-α in combination with IL-2 or IFN-γ and of CD4+ multifunctional cells secreting IL-2, TNF-α and IFN-γ. Correlating with the immunological results the strongest reductions of skin lesions sizes were determined by the admixed domains (80 %) and by the chimera (84 %), which also promoted the most pronounced and significant reduction of the parasite load (99.8 %). Thus, the epitope presentation in a recombinant chimera optimizes immunogenicity and efficacy above the levels induced by the independent or admixed F1 and F3 domains. The multiparameter analysis disclosed that the Th1-CD4+ T helper response induced by the chimera is mainly directed against its FRYPRPKHCHTQVA epitope. Additionally, the YPPEFKTKL epitope of F1 induced the second most important CD4+ T cell response, and, followed by the DVAGIVGVPVAAGCT, FMLQILDFYTKVYE and ELLAITTVVGNQ sequences, also the most potent CD8+ T cell responses and IL-10 secretion. Remarkably, the YPPEFKTKL epitope shows high amino acid identity with a multipotent PADRE sequence and stimulates simultaneously the CD4+, CD8+ T cell and a probable T regulatory response. With this approach we advanced in the design of a nucleoside hydrolase NH36 polytope vaccine capable of inducing cross-protection to cutaneous leishmaniasis.